Kajian Konsep Zero Complaint Untuk Meningkatkan Minat Beli Ulang pada Program Studi di Universitas Semarang - Kuswardani DC; Yani TE; Nurhidayati Nurhidayati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
This study aims to contribute to the understanding of increasing interest in repurchasing the University of Semarang Higher Education services. The variables tested to increase the Repurchase Interest directly are Switching Cost and Perceived Quality. The indirect variable to increase repurchase interest is student satisfaction through Perceived Quality and Service Recovery. The population is all students using USM Higher Education services as many as 25,302 active students, while a sample of 100 respondents using purposive sampling technique. The analytical tool used is Structural Equation Medelling (SEM) with Partial Least Square (PLS) program applications, namely smartPLS.3.0. The results of hypothesis testing indicate that Hypothesis 1 is rejected, while the other hypotheses are supported. Switching Cost has no significant effect on Repurchase Interest. Perceived Quality and Service Recovery is not directly influential on Repurchase Interest, mediated by Student Satisfaction. Student Satisfaction and Service Recovery have a direct effect on Repurchase Interest.